The Development Of Mathematical Competence Of Students Of Higher Education - Barno Abdullaeva, Jamshid Fayzullaev, Khusniddin Shodmonov (International Journal of Advanced Science and Technology, 2020)
The article reveals with the issues based on instructing higher science of understudies in a higher education. Competences for specialized bearings of preparing lone rangers and masters, shaped within the course of higher arithmetic, are defined. The standards of test learning are defined. The highlights of the substance of the exploratory course of higher arithmetic on the illustration of the Direct space segment are considered. Deliberate materials giving an arrangement of the characterized competences are portrayed.